Associations between condylar fractures and external auditory canal fracture: A 7-year retrospective study. Issue 2 (February 2022) - Jiang, Yan; Jiang, Canyang; Huang, Xiaohong; Huang, Jianping; Shi, Bin; Zhu, Xiaofeng; Lin, Lisong; Huang, Li
Abstract: The study aimed to investigate whether the incidence rate of external auditory canal (EAC) fracture varies among different clinical types of condylar fracture. A retrospective cohort study was conducted in single hospital of China. Eligible patients diagnosed with mandibular condylar fractures were retrospectively reviewed. Among all patients with condylar fractures (318 cases and 437 sides), 45 cases and 59 sides (59/437 sides, 13.5%) were found with EAC fracture, including 17(17/38, 44.7%) sides of sagittal fracture of condyle (Type I), 21(21/59, 35.6%) sides of intracapsular condylar fracture (Type II), 8 (8/306, 2.6%) sides of condylar neck fracture (Type III), and 6 (6/34, 17.7%) sides of condylar base fracture (Type IV). Type III condylar fracture had a significant lower rate of EAC fracture than all other three types (all p <0.001). Type I condylar fracture had a higher rate of EAC fracture compared to Type IV ( p =0.014). The incidence rates of EAC fracture in combined Type I+Type II group (38/97, 39.2%) was significantly higher than Type III (8/306, 2.6%, p <0.001) and Type IV (6/34, 17.7%, p =0.002). A total of 35 sides (27 patients) with combined fractures were followed up for 6 months after treatment, among whom 11 sides (7 patients) were operated for both fractures simultaneously. Neither EAC stenosis nor hearing loss was observed. Meanwhile, for 24 non-operated ears from 20 patients, all EACs showed different degrees of stenosis. In conclusion, oral and maxillofacial surgeons should pay more attention to EAC fracture combined with condylar fracture, especially for patients diagnosed with condylar head fracture. Maxillofacial fractures should be accompanied by early treatment of EAC fractures, in order to prevent EAC stenosis, hearing loss, and other complications.